2019
DOI: 10.1177/1687814019883787
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental studies on wrinkling control methods of sheet metal part with high curvature and large flange in rubber forming

Abstract: Wrinkling is one of the main failure modes in sheet metal forming process and may lead to assembly problems of the parts. Control of wrinkling is difficult due to the complex deformation behavior of the sheet metal. A finite element model for side blankholder method to control wrinkling was established and used for the simulation. Trials and simulations were conducted to analyze the parameters of wrinkling characteristics. Results show that with the increase in the angle of the side blankholder, the resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Chen et al [ 121 , 122 ] investigated the wrinkling behavior of high curvature, large flange sheet metal stampings by experiment. They found that if the blank holder was not used, the larger the gap between mold and side blank, and the more serious the wrinkling of the flange.…”
Section: Deformation Instability Induced By the Structural Geometry O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [ 121 , 122 ] investigated the wrinkling behavior of high curvature, large flange sheet metal stampings by experiment. They found that if the blank holder was not used, the larger the gap between mold and side blank, and the more serious the wrinkling of the flange.…”
Section: Deformation Instability Induced By the Structural Geometry O...mentioning
confidence: 99%
“… Wrinkling behavior of sheet metal stamping: ( a ) sheet metal stamping of a high curvature large flange [ 121 , 122 ]; ( b ) wrinkling of GPa-grade steel, comparison analysis of representative wrinkle area (wrinkling area b, c and d) with the simulation results [ 123 ]; ( c ) failure mode of a AA2024-T3 thin plate [ 124 ]. …”
Section: Figurementioning
confidence: 99%
“…Chen et al(2012) conducted finite element analysis of the rubber forming process of high shrinkage bending edges in ABAQUS software, where the results showed that the greater the distance between the side blank holder and the die, the easier the material to wrinkle. According to Chen et al(2019), the finite element analysis of rubber forming wrinkle defects of large curvature and high-flip sheet metal parts was carried out by PAMSTAMP software to determine the optical parameters of side blank holder, the structure of the die, hardness of the rubber, etc., providing a rubber forming method that can directly use the complete machining of convexly curved parts without margin unfolding blanks. explored the consequences of the rubber forming for the simplified models of different convex curved edge by finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…One of the commonly used tools is Finite Element Analysis (FEA) that can simulate and analyze the forming behaviors under different conditions. [18][19][20][21][22][23] In addition, the optimization methods have also been applied to predict forming behaviors in the deep-drawing process. [24][25] This paper integrated FEA and optimization methods to predict the effects of VCOF on formability in deepdrawing.…”
Section: Introductionmentioning
confidence: 99%